Pengaruh Komunikasi Terapeutik yang dilakukan oleh perawat terhadap tingkat kecemasan pasien yang mengalami Hospitalisasi di RSU se-Kabupaten Jember - Siswoyo Siswoyo; Roymond H. Simamora (Jurnal Ilmu Kesehatan Masyarakat, 2009)
Anxiety is a condition where individual or group has anxious feeling (estimate/opinion) and the act of nervous system to respond a vague threat,non-spesific.This research uses Pre-Experiment design with a frame of Pre-Post Test design without control,purpose to identify the influence of therapheutic communication toward the decrease of patient’s anxiety level for Pre-Operation patients cured in Surgery Room RSU in Jember Regency using Consecutive Sampling technigue. The intervention process uses introduction of analytical therapheutic communikative intraction process. A result of the process applies on regres test on which t calculation is much bigger than t table, that is 4,479 > 2,093. In conclusion, every Pre-operation patient has anxiety, and therapheutic communication give meaningful and significant influence to decrease Pre-operation of patient’s anxiety level. As remmendation, in this research, the therapheutic communication done well will be able to decrease patien’s anxiety level so it must be applied in nursing service especially Pre-operation. Key word: Therapheutic Communication, Anxiety